PEMANFAATAN LAHAN SELA PADA BUDIDAYA JERUK SISTEM TANAM RAPAT DI BANYUWANGI - Lyli Mufidah; Emi Budiyati; Sutopo Sutopo (Universitas Muhammadiyah Purwokerto, 2020)
The high deficit in the trade balance value for citrus commodities can be an indication of the need for improvements in production and especially on the quality of citrus in Indonesia. Citrus cultivation with high density cropping system (SITARA) can be one of the strategies to increase production without increasing the area of planting land. The additions of intercropping in this system can be a solution for farmers' income, when citrus plants have not yet produced. Therefore, this study was aimed to analyze the costs and benefits of intercropping cultivation done between SITARA citrus plants with three cropping patterns (geometry) and intercropping plants which stated into four packages: (1) 4x4 (double) with chili intercropping, (2) 4x4 (double) variations (watermelon, tomatoes, broccoli, mustard greens: (3) 3x4 (double) with chili, (4) 3x4 (double) soybean. The results of the analysis showed that the 4x4 m cropping pattern intercroped with watermelon, tomatoes, broccoli and green mustard provide the highest profit of Rp. 13,677,396 per 0,25 ha per year. Although the total R / C ratio is still smaller than chili, but with variations the price decline in one commodity can be supported by other commodities. This pattern turns out to be the one that provide better citrus growth than the other four patterns, which can be seen from the rootstock and scion diameter also the average plant height that is 52, 43 dan 228 cm, respectively. This can ben an indication that intercropping can be done without harming the main crop, if it gets the right treatment. To support the results, the interaction of trees (in this case citrus), soil and seasonal crops can be evaluate more deeply.